Ethnobotanical exploration of medicinal plants in the Himalayan temperate forests of Veshew range, Kulgam, Jammu & Kashmir, India: diversity, utilization, and health significance - Mansoor, Aamir; Mir, Bilal Ahmad; Banoo, Maqsooma; Banoo, Shahar; Peer, Latif Ahmad (Ethnobotany Research and Applications, 2025)
Background: For centuries, medicinal plants have been integral to healthcare, especially in regions with limited modern medical facilities. The Veshew forest range in Kulgam, Jammu and Kashmir, India, has been a significant source of plant-based medicine for local communities, who rely on traditional knowledge to address their healthcare and livelihood needs, including food, fodder, timber, and other essential resources. Methods: This study used field surveys, semi-structured interviews, and questionnaires from the Veshew forest range to document the medicinal uses of plants. Ethnobotanical indices, including the Informant Consensus Factor (ICF) and Use Value (UV), were applied to analyze the efficacy and consensus of traditional knowledge regarding these plants. Results: This study documented 34 medicinally significant plant species distributed across 18 families and 32 genera, with Asteraceae and Lamiaceae emerging as the dominant families. Prominent species included Portulaca oleracea, Iris kashmiriana, Taraxacum officinale, Solanum nigrum, Prunella vulgaris, Allium sativum, Brassica rapa, Trigonella foenumgraecum, Trifolium pratense, and Lavatera kashmiriana. Informants frequently cited these plants for their therapeutic applications in treating ailments such as skin irritation, digestive issues, jaundice, and diarrhea. Notably, high ICF values (0.88) for endocrine disorders and 100% fidelity levels (FL) for species like Lavatera kashmiriana (skin irritation), Taraxacum officinale (jaundice), and Iris kashmiriana (diarrhea) underscore their cultural importance and medicinal efficacy within the local healthcare system. Conclusions: This ethnobotanical exploration highlights the rich traditional knowledge of medicinal plants in the Veshew range, stressing the importance of documentation for preserving indigenous practices, bridging generational knowledge gaps, and preventing the loss of valuable plant species. Further pharmacological studies are needed to validate these medicinal uses. Keywords: Herbal medicine, Traditional knowledge, Ethnomedicine, Veshew, Kulgam, Biodiversity, Kashmir Himalaya.